The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1478-3231.2009.02061.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of OAS‐1 determines liver fibrosis progression in hepatitis C by reduced ability to inhibit viral replication

Abstract: The SNP of OAS-1 at the exon 3 of its coding sequence was associated with progression of disease in Japanese patients with HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
21
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 42 publications
2
21
0
Order By: Relevance
“…Variants in MYL2 and C12orf51 also showed strong association with HDLc in this study. OAS1, encoding an enzyme of the innate immune system, has an antiviral function 6 . It has been reported that polymorphisms of OAS1 are involved in the progression of disease after hepatitis C virus infection 6 l e t t e r s 0.0008).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Variants in MYL2 and C12orf51 also showed strong association with HDLc in this study. OAS1, encoding an enzyme of the innate immune system, has an antiviral function 6 . It has been reported that polymorphisms of OAS1 are involved in the progression of disease after hepatitis C virus infection 6 l e t t e r s 0.0008).…”
mentioning
confidence: 99%
“…OAS1, encoding an enzyme of the innate immune system, has an antiviral function 6 . It has been reported that polymorphisms of OAS1 are involved in the progression of disease after hepatitis C virus infection 6 l e t t e r s 0.0008). The protein encoded by ZNF827 may be a transcriptional regulator that affects plasma GGT levels.…”
mentioning
confidence: 99%
“…Several biomarkers have recently been evaluated in the context of HCV infection, including interferon-responsive genes (26,30,37,40,51,53), chemokines (28,29,31,54,56), interleukin-28B (IL-28B) gene polymorphisms (16,18,39), fibrosis protein markers (6,7,35), fibrinogen-like protein 2 (11), complement component C3a (25), and osteopontin (23).…”
mentioning
confidence: 99%
“…(37)(38)(39) Gene polymorphisms associated with activity of hepatitis and liver fibrosis progression, which contribute to the development of HCC, have also been reported in HCV patients. (40,41) In spite of this effort, most studies had insufficient sample sizes, and the associations with HCV-related HCC were not robust. Therefore, better predictive genetic markers are still needed.…”
Section: Epidemiology and Risk Factors Of Hccmentioning
confidence: 99%